The Ability of Using Diction in Junior High School Students’ Poetry - Ibna Ul Izzati, Siti Maryam & Agus Supriatna (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2019)
This article discusses students' ability in using word choices (diction) on the poetry of students of SMP Negeri 3 Cianjur. The method used in this research is descriptive qualitative method. The techniques used are test and questionnaire. The population of the study is 25 students of class VIII-4. This study concludes that the students’diction ability is 78 (it can be categorized as good). In terms of diction aspects,  formal aspect has very good criteria, synonymy has good criteria, and polysemy has sufficient criteria. Obstacles experienced by students in writing poetry that includes diction aspect and its problem solving.Keywords: diction, formal aspect, polysemy, synonymy.